Cerebral Microbleeds During Transcatheter Aortic Valve Replacement: A Prospective Magnetic Resonance Imaging Cohort. Issue 5 (20th June 2022) - Van Belle, Eric; Debry, Nicolas; Vincent, Flavien; Kuchcinski, Grégory; Cordonnier, Charlotte; Rauch, Antoine; Robin, Emmanuel; Lassalle, Fanny; Pontana, François; Delhaye, Cédric; Schurtz, Guillaume; JeanPierre, Emmanuelle; et al.
Abstract : Background: Cerebral microbleeds (CMBs) have been observed in healthy elderly people undergoing systematic brain magnetic resonance imaging. The potential role of acute triggers on the appearance of CMBs remains unknown. We aimed to describe the incidence of new CMBs after transcatheter aortic valve replacement (TAVR) and to identify clinical and procedural factors associated with new CMBs including hemostatic measures and anticoagulation management. Methods: We evaluated a prospective cohort of patients with symptomatic aortic stenosis referred for TAVR for CMBs (METHYSTROKE [Identification of Epigenetic Risk Factors for Ischemic Complication During the TAVR Procedure in the Elderly]). Standardized neurologic assessment, brain magnetic resonance imaging, and analysis of hemostatic measures including von Willebrand factor were performed before and after TAVR. Numbers and location of microbleeds on preprocedural magnetic resonance imaging and of new microbleeds on postprocedural magnetic resonance imaging were reported by 2 independent neuroradiologists blinded to clinical data. Measures associated with new microbleeds and postprocedural outcome including neurologic functional outcome at 6 months were also examined. Results: A total of 84 patients (47% men, 80.9±5.7 years of age) were included. On preprocedural magnetic resonance imaging, 22 patients (26% [95% CI, 17%–37%]) had at least 1 microbleed. After TAVR, new microbleeds were observed in 19 (23% [95% CI, 14%–33%]) patients. The occurrence of new microbleeds was independent of the presence of microbleeds at baseline and of diffusion-weighted imaging hypersignals. In univariable analysis, a previous history of bleeding ( P =0.01), a higher total dose of heparin ( P =0.02), a prolonged procedure ( P =0.03), absence of protamine reversion ( P =0.04), higher final activated partial thromboplastin time ( P =0.05), lower final von Willebrand factor high-molecular-weight:multimer ratio ( P =0.007), and lower final closure time with adenosine–diphosphate ( P =0.02) were associated with the occurrence of new postprocedural microbleeds. In multivariable analysis, a prolonged procedure (odds ratio, 1.22 [95% CI, 1.03–1.73] for every 5 minutes of fluoroscopy time; P =0.02) and postprocedural acquired von Willebrand factor defect (odds ratio, 1.42 [95% CI, 1.08–1.89] for every lower 0.1 unit of high-molecular-weight:multimer ratio; P =0.004) were independently associated with the occurrence of new postprocedural microbleeds. New CMBs were not associated with changes in neurologic functional outcome or quality of life at 6 months. Conclusions: One out of 4 patients undergoing TAVR has CMBs before the procedure and 1 out of 4 patients develops new CMBs. Procedural or antithrombotic management and persistence of acquired von Willebrand factor defect were associated with the occurrence of new CMBs. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02972008.